Controllable-permittivity and high-tunability of Ba0.5Sr0.5TiO3/MgO based ceramics by composite configuration - Tang, Linjiang (2013)
Ba0.5Sr0.5TiO3 (BST50)/MgO composites, with 2-2-type configurations, consisting of BST layers and MgO layers, were fabricated by using tape-casting and laminating technique. Microstructure, dielectric response, and tunable properties of the 2-2-type composites were investigated. An important feature of the 2-2 type composites is that DC fields can be effectively applied to the high-permittivity ferroelectric phase when the fields are applied in parallel direction to the inter-phase boundaries. As a result, with increasing volume fraction (q) of MgO, tunability of the composites remained almost unchanged, whereas their permittivity value could be reduced significantly. This behavior has not been observed in the conventional 3-0 type composites